Analisis Kepentingan Tiongkok dalam Kebijakan Belt and Road Initiative di Pakistan - Krisman Heriamsal; Asma Amin; Muhammad Rizky Prawira (Indonesian Journal of Peace and Security Studies (IJPSS), 2021)
This study aims to analyze China's interests in the Belt and Road Initiative (BRI) policies in Pakistan. Currently, Pakistan is China's strategic partner in the implementation of the BRI project. The infrastructure development in several sectors in Pakistan is being carried out massively through direct loans from China. This certainly raises questions regarding China's interests in Pakistan and this study attempts to answer these questions. This study uses descriptive qualitative research methods with literature study as the data collection technique. To analyze the case, this study applies offensive realism theory, with the concepts of hegemony, and national interest. The results of this study indicate that China's efforts in Pakistan are actually a form of Chinese active maneuvers in achieving its interests, namely hegemony. Through the BRI project, China can connect with the largest oil-producing countries in order to meet its high industrial needs. Second, the connectivity created by BRI enables China to increase its force capability in the South Asian region. Third is political interests, in which China can create a positive image to substantially increase its diplomatic power and strengthen its international status. Lastly, the ideological interest in which China uses slogans such as the 'Chinese Dream' for the stability and legitimacy of Xi Jinping and the Chinese Communist Party over their domestic society